Persepsi terhadap kompetensi pensyarah penyelia : satu kajian di sebuah maktab perguruan - Khadijah, Bte. Hj. Tompang (1997)
The main objective of this study is to examine the perceived competency level and competency needs lecturers as supervisors of trainee teachers at Maktab Perguruan Perempuan Melayu Melaka. The study was also to determine respondent's ranking of competencies needed in order to perform their task efficiently and effectively.